Vitality, Self-healing and Ecology: The Flow of Naturopathic Thought Across the United States and India. (January 2020) - Sheldon, Victoria
Abstract: For over 5, 000 years, the region now known as India has held a rich reservoir of medical systems, each providing distinct orientations towards illness experience, aetiology, cure and prevention. Since the turn of the twentieth century, there has been a considerable rise in the cultural recontextualisation of European and North American medical traditions in South Asia. With a focus on the guiding concepts of vitality, self-healing and ecology, this article maps the transnational trajectories of naturopathy across three sites: its instantiation into the United States' early 1900s cultural climate of health epidemics and industrialisation; its rearticulation into the context of Gandhian anti-colonial movements in India; and its transformation into a mode of asserting public health and environmental advocacy in contemporary India. After tracing the trajectory of naturopathic thought, this article will provide a practitioner profile of naturopathy Dr Jacob Vadakkanchery as well as a framing of his politicised response to the 2018 floods in Kerala, south India. This particular examination serves as a microcosm of a larger trend: contemporary practitioners in India overtly re-frame naturopathic concepts in relation to immanent environmental and public health concerns.